PROFITABILITAS, LIKUIDITAS, DAN INVENTORY INTENSITY TERHADAP TAX AVOIDANCE: PERAN MODERASI UKURAN PERUSAHAAN - Annisa Maulidinov; Muhammad Irfan Tarmizi (Media Riset Bisnis Ekonomi Sains dan Terapan, 2026)
This study aims to examine the effects of profitability, liquidity, and inventory intensity on tax avoidance, with firm size as a moderating variable, among consumer goods manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period 2020-2024. This research employs a quantitative approach, using panel data regression analysis and Moderation Regression Analysis (MRA) in EViews 12. The sample consists of consumer goods manufacturing companies selected through purposive sampling. The results show that profitability has a significant negative effect on tax avoidance, while liquidity has no significant effect on tax avoidance. Inventory intensity has a significant positive effect on tax avoidance. Firm size is unable to moderate the relationship between profitability, liquidity, and inventory intensity on tax avoidance. The findings suggest that companies with higher profitability tend to comply with tax obligations, while companies with higher inventory intensity tend to utilize storage and maintenance costs as tax deductions.Keywords: firm size, inventory intensity, liquidity, profitability, tax avoidance)